1997
DOI: 10.1148/radiology.204.2.9240540
|View full text |Cite
|
Sign up to set email alerts
|

Atypical ductal hyperplasia diagnosed at stereotactic breast biopsy: improved reliability with 14-gauge, directional, vacuum-assisted biopsy.

Abstract: ADH was diagnosed 2.7 times more reliably at vacuum-assisted biopsy than at large-core biopsy (with no increase in complications) with most of the improvement as a result of acquisition of more than 10 specimens per lesion, but carcinoma was sufficiently underestimated with both methods to necessitate surgical biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
108
3
7

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(128 citation statements)
references
References 0 publications
10
108
3
7
Order By: Relevance
“…In the current study, the underestimation rate was 45.9% (34/74), which comprised a 50.0% (25/50) rate for 14-gauge automated gun biopsies and a 37.5% (9/24) rate for 11-gauge vacuum-assisted biopsies (P = 0.314 for the two methods). Many studies have investigated stereotactic biopsies, and taking larger core specimens or using the vacuum-assisted device is believed to improve accuracy [20][21][22]. However, there are few reports regarding ultrasound-guided procedures, and the benefit of vacuumassisted devices remains debatable.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the underestimation rate was 45.9% (34/74), which comprised a 50.0% (25/50) rate for 14-gauge automated gun biopsies and a 37.5% (9/24) rate for 11-gauge vacuum-assisted biopsies (P = 0.314 for the two methods). Many studies have investigated stereotactic biopsies, and taking larger core specimens or using the vacuum-assisted device is believed to improve accuracy [20][21][22]. However, there are few reports regarding ultrasound-guided procedures, and the benefit of vacuumassisted devices remains debatable.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 These results have contributed to the recommendation that follow-up surgical excision be performed when ADH is detected on core biopsy. 15,16 LN encompasses a spectrum of disease ranging from minimal atypical lobular hyperplasia (ALH) to lobular carcinoma in situ (LCIS). 17 The reported incidence of LN in excisional biopsy samples ranges from 0.5-3.9%.…”
mentioning
confidence: 99%
“…However, the automated biopsy findings for ADH are less reliable because of histologic underestimation of malignancy. The rate of underestimation of ADH has been reported to range from 11% to 65% for 14-gauge automated biopsy (14)(15)(16)(17)(18)(19)(20). Technical advances in percutaneous core needle biopsy, such as increasing needle diameter from 14-gauge to 11-gauge and adding a vacuum device, have allowed larger samples of tissue to be obtained (5,6), substantially improving the accuracy of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Jackman et al (16) reported that the risk of underestimation with SVAB increased with the size of the lesion. They also found that the risk of underestimation did not increase with the maximum size of the lesion for ADH, with SVAB (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation